2020
DOI: 10.3390/ijms21041234
|View full text |Cite
|
Sign up to set email alerts
|

mRNA with Mammalian Codon Bias Accumulates in Yeast Mutants with Constitutive Stress Granules

Abstract: Stress granules and P bodies are cytoplasmic structures assembled in response to various stress factors and represent sites of temporary storage or decay of mRNAs. Depending on the source of stress, the formation of these structures may be driven by distinct mechanisms, but several stresses have been shown to stabilize mRNAs via inhibition of deadenylation. A recent study identified yeast gene deletion mutants with constitutive stress granules and elevated P bodies; however, the mechanisms which trigger its fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…TT foci formed in the absence of THO/TREX-2 were, but are no longer considered to be "constitutive stress granules". Further studies have revealed that, in contrast to genuine SGs, TT foci were formed by a distinct mechanism and, similar to REGs, they contain aberrant mRNPs (see Box 6), which have been exported from the nucleus (Eshleman et al, 2016;Kozlova et al, 2020).…”
Section: Sgs-like Particlesmentioning
confidence: 99%
“…TT foci formed in the absence of THO/TREX-2 were, but are no longer considered to be "constitutive stress granules". Further studies have revealed that, in contrast to genuine SGs, TT foci were formed by a distinct mechanism and, similar to REGs, they contain aberrant mRNPs (see Box 6), which have been exported from the nucleus (Eshleman et al, 2016;Kozlova et al, 2020).…”
Section: Sgs-like Particlesmentioning
confidence: 99%
“… 6 , 7 , 8 Human malignancies are linked to epigenetic alterations in RNA that aren't properly controlled. m7G has been identified to take a significant role in BC in previous research, and several genes, such as NSUN2 9 and the METTL1 gene, 10 are known to adversely regulate m7G. METTL1 methyltransferase mediates m7G methylation within let‐7e miRNA, activating the let‐7e miRNA/HMGA2 axis which was linked with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…METTL1 methyltransferase mediates m7G methylation within let‐7e miRNA, activating the let‐7e miRNA/HMGA2 axis which was linked with a poor prognosis. Meanwhile, other m7G‐related genes, such as DCP2 10 and DCPS, may cause illness by committing the transcript to destruction. However, it is unclear if these m7G‐regulated genes are associated with the prognosis of BC samples.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue is concluded by two experimental papers describing how DNA methylation can be a source of variability in the expression of rRNA genes [26] and how codon bias can be a triggering factor for the accumulation of specific mRNAs into stress bodies in yeast [27]. Both articles are prime examples of how genomic variability can alter the structure and function of RNA regulatory networks.…”
mentioning
confidence: 99%